Schooling Decisions in Indonesia: a Lesson From Indonesian Crisis - Bayu Kharisma; Ferry Hadiyanto; Sutyastie Soemitro Remi (Signifikan: Jurnal Ilmu Ekonomi, 2020)
This research aims to analyze the role of income shocks, gender, and resource competition between siblings against the school's decision at the level of primary and senior secondary education during the economic crisis in Indonesia. Methods in this research were conducted in two phases, fixed effect and conditional logit. Results reveal that no evidence of households' transitory income affected children's education level, both for primary and senior secondary education. Meanwhile, compared to boys, girls have a higher probability of dropping out of school and have lower school enrollment rates in primary education. This paper indicated the existence of resource competition between the younger child and the older child for education, especially for senior secondary education.JEL Classification: I20, I24, I25, J16How to Cite:Kharisma, B., Hadiyanto, F., & Remi, S. S. (2020). Schooling Decision in Indonesia: a Lesson From Indonesian Crisis. Signifikan: Jurnal Ilmu Ekonomi, Vol. 9(1), 81-92. doi: http://dx.doi.org/10.15408/sjie.v9i1.12479.